Social Policy Review 29 : Analysis and Debate in Social Policy, 2017 - Heins, Elke; Needham, Catherine, 1974-; Hudson, John, 1972- (Book collections on Project MUSE., 2017)
'Social Policy Review' is an annual publication that offers contributions from a mix of internationally prominent experts in social policy focusing on the economic and political challenges that confront governments and the diverse ways that they have responded. It offers the most up-to-date and comprehensive picture available of the current state of social policy and research.